Kvizi iz Matematike I: 2. del - Tepeh, Aleksandra (2024)
Mathematics 1 Quizzes: Part Two. The present collection of solved exercises is an educational tool primarily intended for first-year students of the Computer Science and Information Technologies and Informatics and Technologies of Communication study programs at the University of Maribor's Faculty of Electrical Engineering and Computer Science (UM FERI) who are taking the subject Mathematics 1. Since most natural science and technical study programs at other faculties cover the same material in the first year, it is also intended for a broader audience. The first part of the collection covers topics in basic logic, sets, complex numbers, and functions. The second part represents its continuation and deals with limits, derivatives, integrals, sequences, and series. It encourages students to prepare good notes, which is one of the foundations for successful exam preparation.
Keywords: functions; limits; derivatives; integrals; sequences; series